Elevated Atmospheric CO2 Concentration Improved C4 Xero-Halophyte Kochia prostrata Physiological Performance under Saline Conditions - Rakhmankulova, Zulfira; Shuyskaya, Elena; Toderich, Kristina; Voronin, Pavel (Plants, 2021)
A significant increase in atmospheric CO2 concentration and associated climate aridization and soil salinity are factors affecting the growth, development, productivity, and stress responses of plants. In this study, the effect of ambient (400 ppm) and elevated (800 ppm) CO2 concentrations were evaluated on the C4 xero-halophyte Kochia prostrata treated with moderate salinity (200 mM NaCl) and polyethylene glycol (PEG)-induced osmotic stress. Our results indicated that plants grown at elevated CO2 concentration had different responses to osmotic stress and salinity. The synergistic effect of elevated CO2 and osmotic stress increased proline accumulation, but elevated CO2 did not mitigate the negative effects of osmotic stress on dark respiration intensity and photosystem II (PSII) efficiency. This indicates a stressful state, which is accompanied by a decrease in the efficiency of light reactions of photosynthesis and significant dissipative respiratory losses, thereby resulting in growth inhibition. Plants grown at elevated CO2 concentration and salinity showed high Na+ and proline contents, high water-use efficiency and time required to reach the maximum P700 oxidation level (PSI), and low dark respiration. Maintaining stable water balance, the efficient functioning of cyclic transport of PSI, and the reduction of dissipation costs contributed to an increase in dry shoot biomass (2-fold, compared with salinity at 400 ppm CO2). The obtained experimental data and PCA showed that elevated CO2 concentration improved the physiological parameters of K. prostrata under salinity.